SEJARAH LEMBAGA KEUANGAN DALAM ISLAM - Syai’in, - - (Irtifaq, 2015)
In the times of financial institutions in general, it has developed so rapidly. Similarly, the financial institution in Islam, something revolutionary that is carried the Prophet Muhammad is the establishment of a depository institution called Bayt al-Mal, whose function is to receive the income and expenditure transparent. Umar was also known for fairness and thoroughness that supervision be authoritative institution under his rule. He dropped himself whether market mechanism works properly, rebuked those who seek profits in a way that is not true and congratulated the honest merchant. Only one caliph in this dynasty were admired for justice and piety, namely Umar bin Abdul Aziz, also known as Umar II. In the short reign, about 2.5 years, he was able to distribute income countries such that it can be welfare of its people. It is said that because sejahteranya people at that time so hard to find people who receive zakat. Keywords: Financial Institutions, Bayt al-Ma>l